Pore network simulation of HT-PEMFC GDL using radical Voronoi tessellation: Analysis of oxygen, phosphoric acid solution, and charge transport - Zhang, Wei; Lu, Xiang; Bück, Andreas; He, Zhixia; Tsotsas, Evangelos; Zhaochen, Jiang (International Journal of Heat and Mass Transfer, 2025)
Accurate construction of the porous structures within the gas diffusion layer (GDL) in fuel cells is significant for unveiling mass transport mechanisms within porous media and enhancing the design of GDLs. A new pore network construction method (PNCM) that couples the maximum sphere (MS) and radical Voronoi tessellation (RVT) was developed based on the three-dimensional morphology of the GDL obtained through micro-CT reconstruction. Different porosities can be obtained for various fiber diameters by adjusting the number of pores. The new MS-RVT pore network model (MS-RVT PNM) is used to investigate the impact of inlet liquid coverage ratio, hydrophilic pore fraction, fiber diameter, and porosity on liquid saturation, effective gas diffusion coefficient, and voltage loss within GDLs of high-temperature proton exchange membrane fuel cells (HT-PEMFCs). It was found that smaller-diameter fiber GDLs can effectively facilitate phosphoric acid solution discharge and have a greater gas diffusion coefficient, while larger-diameter fiber GDLs improve the distribution of gas–liquid two-phase pathways. The optimal hydrophilic pore fraction for GDLs is 0.4, and the optimum porosity is always around 0.55 as the current density increases from 1 to 4 A/cm2. A comparative analysis of different PNMs reveals that commonly used regular PNMs tend to overestimate the liquid saturation of GDLs and concentration loss, but underestimate the effective oxygen diffusion coefficient and ohmic loss. The conclusions are of great significance for guiding the optimization of GDL design in HT-PEMFCs.
CRIS-Team Scopus Importer:2025-04-11
Keywords: HT-PEMFC; Maximum sphere; Pore network models; Radical Voronoi tessellation; Transport phenomena in porous media